Syndrome of inappropriate antidiuretic hormone secretion and cerebral salt wasting as the common causes of hyponatremia in tertiary care hospital - Bade, Yogesh Pralhad; Chaudhari, Harishchandra Rameshchandra (International Journal of Advances in Medicine, 2020)
Background: Hyponatremia is a typical condition of electrolyte disturbance that may be euvolemic, hypovolemic or hypervolemic. Proper interpretation through laboratory tests helps to differentiate the types and causes of hyponatremia. This study was conducted to evaluate the syndrome of inappropriate antidiuretic hormone secretion (SIADH) and cerebral salt wasting (CSW) as the common causes of hyponatremia in tertiary care hospital. Methods: A prospective interventional study was conducted, including hyponatremia cases, admitted in NTU/ICU/CCU and other medical wards at Ruby Hall Clinic from August 2011 to December 2013. Results: Of 150 patients enrolled in this study, 33.33% patients were euvolemic, 34% patients were hypervolemic and 32.66% patients were hypovolemic. For the euvolemic patients, SIADH (68%) was the most common cause; whereas, CSW (34.39%) was the common cause for hypovolemic type of hyponatremia. Stroke was found to be the most common cause of SIADH (55.88%), Intra-cerebral bleeding was observed to be the most common causative factor between SIADH and CSW associated hyponatremia. Conclusions: Hyponatremia in central nervous system disorder patients frequently occurred due to SIADH and CSW. Most common cause of SIADH was stroke and for CSW it was intra cerebral bleed.